Electrically switchable band-edge laser based on polymer-stabilized blue phase liquid crystal. Issue 2 (26th January 2021) - Hou, De-Shan; Cao, Jia-Xin; Li, Xuan; Zhu, Ji-Liang; Han, Wen-Ming
ABSTRACT: An electrically switchable band-edge laser has been demonstrated in a dye-doped polymer-stabilised blue phase liquid crystal. The light intensity of the laser can be tuned in three-dimensional space with a switching time of submillisecond, which promotes this band-edge laser widespread use in displays, point-of-care biomedical analysis, and optical security coatings. Graphical abstract: uf0001